2003
DOI: 10.4049/jimmunol.170.5.2663
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptors in Human Airway Smooth Muscle Cells Has a Superior Anti-inflammatory Profile to Corticosteroids: Relevance for Chronic Obstructive Pulmonary Disease Therapy

Abstract: Airway smooth muscle is actively involved in the inflammatory process in diseases such as chronic obstructive pulmonary disease and asthma by 1) contributing to airway narrowing through hyperplasia and hypertrophy and 2) the release of GM-CSF and G-CSF, which promotes the survival and activation of infiltrating leukocytes. Thus, the identification of novel anti-inflammatory pathways in airway smooth muscle will have important implications for the treatment of inflammatory airway disease. This study identifies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
122
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 52 publications
3
122
1
3
Order By: Relevance
“…26,27 In smooth muscle cells PPAR-c activation has additional anti-inflammatory effects compared with the effects of corticosteroids. 28 We demonstrated that PPARc was expressed by eosinophils and that PPAR-c agonists were able to inhibit eosinophil chemotaxis and antibodydependent cellular cytotoxicity reactions in vitro. 29 Furthermore, in a murine model of asthma, treatment with a PPAR-c agonist also inhibited the development of allergic inflammation, including pulmonary eosinophilia and airway AHR.…”
mentioning
confidence: 87%
“…26,27 In smooth muscle cells PPAR-c activation has additional anti-inflammatory effects compared with the effects of corticosteroids. 28 We demonstrated that PPARc was expressed by eosinophils and that PPAR-c agonists were able to inhibit eosinophil chemotaxis and antibodydependent cellular cytotoxicity reactions in vitro. 29 Furthermore, in a murine model of asthma, treatment with a PPAR-c agonist also inhibited the development of allergic inflammation, including pulmonary eosinophilia and airway AHR.…”
mentioning
confidence: 87%
“…13,36,37 Long-term effects include subepithelial fibrosis and epithelial metaplasia. 89 Both the type 2 T helper cell Fig.…”
Section: Asthmamentioning
confidence: 99%
“…Following their identification, a rapidly increasing number of articles and reviews have been written, including those that focus on PPAR expression, function, and regulation, 2,3 as well as their role in lipid and glucose metabolism, [4][5][6][7] diabetes and obesity, [8][9][10] atherosclerosis, 4,8,11 cellular proliferation/differentiation, [12][13][14][15] neurological diseases, [16][17][18] and inflammation/immunity. 7,[19][20][21] These publications are recommended to readers who want additional information on these topics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations